Bifunctional supramolecular prodrug vesicles constructed from a camptothecin derivative with a water-soluble pillar[5]arene for cancer diagnosis and therapy. Issue 73 (22nd August 2019) - Sun, Guangping; He, Zhimei; Hao, Min; Xu, Zuqiang; Hu, Xiao-Yu; Zhu, Jun-Jie; Wang, Leyong
Abstract : Bifunctional supramolecular prodrug nanocarriers have been successfully constructed for efficient anticancer drug delivery and tumor diagnosis and therapy. Abstract : Bifunctional supramolecular prodrug vesicles have been successfully constructed based on the complexation between a glutathione (GSH)-responsive prodrug guest molecule (DNS-CPT ) and a water-soluble pillar[5]arene (WP5 ) for cancer diagnosis and therapy. Under the microenvironment of cancer cells with high GSH concentration, 7-ethyl-10-hydroxycamptothecin (SN-38) with strong yellow fluorescence can be efficiently released from the prodrugDNS-CPT for drug location and cancer therapy.